2002
DOI: 10.1021/ic025536v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and DNA-Binding Properties of Cationic 2,2‘:6‘,2‘ ‘-Terpyridineplatinum(II) Complexes Containing 1,2- and 1,7-Dicarba-closo-dodecaborane(12)

Abstract: The first examples of DNA metallointercalators containing a dicarba-closo-dodecaborane(12) (carborane) moiety are presented. Treatment of the labile platinum(II) complex [Pt(OTf)(terpy)](+) (terpy = 2,2':6',2' '-terpyridine) with the 1,2-carborane monothiol derivatives 1-HS(CH(2))(n)-1,2-C(2)B(10)H(11) (n = 0, 1) or the novel 1,7-carborane ligand, 1-HSCH(2)-1,7-C(2)B(10)H(11), affords the stable, brightly colored species [Pt(1-S(CH(2))(n)-1,Z-C(2)B(10)H(11))(terpy)](+) (Z = 2, n = 0, 1; Z = 7, n = 1) in good y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 28 publications
(19 reference statements)
0
27
0
Order By: Relevance
“…In contrast, the binding constant for [Pt(o-tolyl-terpy)(2-picoline)] 2+ is reported to be the same as that for [Pt(terpy)(2-picoline)] 2+ , indicating that 4 substituents on the terpy ligand do not affect intercalation [26]. Intercalation into ct-DNA is not prevented by the steric bulk of the carboranethiol ligand in complex cations such as [Pt(terpy)(SCH 2 C 2 B 10 H 11 )] + [27].…”
Section: Mononuclear Complexesmentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast, the binding constant for [Pt(o-tolyl-terpy)(2-picoline)] 2+ is reported to be the same as that for [Pt(terpy)(2-picoline)] 2+ , indicating that 4 substituents on the terpy ligand do not affect intercalation [26]. Intercalation into ct-DNA is not prevented by the steric bulk of the carboranethiol ligand in complex cations such as [Pt(terpy)(SCH 2 C 2 B 10 H 11 )] + [27].…”
Section: Mononuclear Complexesmentioning
confidence: 82%
“…15) are cytotoxic [29,27,67,68] Studies using cisplatin-sensitive human ovarian cancer cell lines and a cisplatin-resistant variant cell line yielded similar IC 50 values, suggesting a cytotoxicity mechanism that differs from that for cisplatin. Complexes in the series differed somewhat in their cytotoxicity, with results suggesting that differences in solubility may be controlling anti-tumor activity [68].…”
Section: Biological Activitymentioning
confidence: 95%
“…[7][8][9][10] Preliminary DNA-binding studies demonstrated that the platinum(II)-carborane complex 1 was able to intercalate calfthymus DNA but not to the same degree as the analogous [Pt(terpy)(SCH 2 CH 2 OH)] + and this was proposed to be the result of steric hindrance due to the bulky closo-carborane functionality. 7 Nevertheless, cell uptake and cytotoxicity experiments with 1 and related complexes revealed promising results. 8 Unfortunately, the aqueous solubility of 1 proved to be extremely limited due to the lipophilicity of the closo-carborane moiety.…”
Section: Introductionmentioning
confidence: 99%
“…[2,24,25] More recently, we have reported the synthesis of a highly water-soluble Pt II complex containing a thiopropyl-1,2-closocarborane functionalized with a pendant glycerol group (1) to improve the many shortcomings previously observed with these types of carborane species. [26] Herein we report the DNA binding properties and cell uptake and distribution of 1 ( Fig.…”
Section: Introductionmentioning
confidence: 99%